Evaluation of Road Network Connectivity in the Aerocity Area of Banjarbaru City: Evaluasi Konektivitas Jaringan Jalan Wilayah Aerocity Kota Banjarbaru - Miftahul Ridhoni; Andi Achmad Priyadharma; Muhammad Yusuf Ridhani; Kiky Permana Setiawan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Road layout is a fundamental framework that shapes the long-term development of a city. A road network with high connectivity provides residents with more efficient travel options and better access to public facilities, while low connectivity tends to increase dependence on private vehicles and extend travel distances. This study aims to measure the connectivity of physical road infrastructure in the Aerocity Area of Banjarbaru City, which is designated as a transportation activity center based on Regional Regulation No. 4 of 2024. The method used is quantitative analysis using three indicators: Road Density Index, Beta Connectivity Index, and Gamma Connectivity Index. Road network data in 2025, including road length, number of segments, and number of intersections, was analyzed using ArcMap software. The analysis results show that the connectivity of the Aerocity Area based on travel route choices is classified as good, with an overall Beta Index value of 1.47 (>1). However, the connectivity cannot be said to be perfect, as indicated by the Gamma Index value of 0.49 (<1). The low Gamma Index value is caused by many road segments that form cul-de-sacs (dead ends) so that they have not been optimally developed. It is lead to the recommendation that although the Aerocity Area has a good choice of routes from the Road Density Index, its structural connectivity still needs to be improved by optimizing intersections and avoiding the development of single-access areas.